PENERAPAN DEMOKRASI PANCASILA DALAM PROSES PEMILIHAN KETUA RT/RW/LPMK DI KOTA SURABAYA - Purwito, Dedy (Jurnal HUKUM BISNIS, 2025)
The city of Surabaya is the second largest metropolitan city with a diverse population of migrants and natives, which often raises various problems, including in terms of leadership at the RT/RW/LKMK level. For example, the problem is what happens when the term of office of the head of the RT/RW/LKMK ends, no one wants to nominate themselves as a replacement and there are no residents to follow up on the issue, so what happens is that the head of the RT/RW/LKMK becomes vacant. Other problems that often occur are complaints related to the management of RT, RW, and LPMK, for example, there are residents who report that the management of RT in their area was not formed through consensus. Some also felt that they were not involved in the RT election. This means that the RT election did not apply the principles of democracy as mandated by Pancasila, the 4th Precept, namely Democracy Led by Wisdom in Consultation/Representation. The principle of democracy, also known as people's sovereignty, guarantees people's participation in the decision-making process, so that any laws and regulations that are implemented and enforced truly reflect the people's sense of justice. In order to anticipate friction in the community and prevent the neighbourhood atmosphere from becoming chaotic, it is necessary to apply the principles of Pancasila Democracy in conducting RT/RW/LPMK elections. The city of Surabaya already has a legal regulation regarding the election of the head of the RT, RW and Kelurahan Community Empowerment Institution (LPMK), namely Peraturan Walikota Surabaya Nomor 112 Tahun 2022 tentang Pembentukan dan Pembinaan Rukun Tetangga, Rukun Warga dan Lembaga Pemberdayaan Masyarakat Kelurahan, which aims to be a guideline for the formation, guidance and supervision of community organisations. Keywords: Pancasila Democracy, principles of democracy, general election of RT/RW/LKMK